An Analysis of Gender-Based Differences in Critical Thinking Skills in Geography Education through a Problem-Based Learning Approach - Ease Arent; Muhammad Affadil; Emelda Thesalonika (EDUJAVARE: International Journal of Educational Research, 2026)
This study is motivated by the importance of instructional innovation in improving students’ learning outcomes in Geography, as well as the potential differences in academic achievement based on gender. Problem-Based Learning (PBL) was selected as it is considered effective in fostering critical thinking, problem-solving, and collaborative skills. This study aims to analyze gender-based differences in Geography learning outcomes at SMP Negeri 1 Gebang through the implementation of PBL. A quasi-experimental method with a nonequivalent control group design was employed. The participants were eighth-grade students, grouped by gender to compare their learning outcomes after experiencing PBL. The research instrument was a validated Geography achievement test. Data were analyzed using an independent samples t-test to determine significant differences between male and female students. The results indicate that PBL effectively improves students’ learning outcomes in Geography. However, a difference was found between male and female students, with female students achieving higher average scores, although both groups showed significant improvement. In conclusion, PBL is effective in enhancing Geography learning outcomes, and gender differences should be considered in designing more inclusive instructional strategies.